DRESS syndrome: A literature review and treatment algorithm (2023)
ABSTRACT: Drug reaction with eosinophilia and systemic symptoms, known by its acronym in English as DRESS (Drug Reaction with Eosinophilia and Systemic Symptoms), clinically manifests with fever, facial edema, lymphadenopathy, a morbilliform rash, and organ involvement. Laboratory results reveal leukocytosis, atypical lymphocytes, eosinophilia, and alterations of liver and kidney function tests. The actual incidence of DRESS is unknown, because it may vary depending on the type of medication and the immune status of each patient; also, because many cases remain undiagnosed or untreated. The drugs most associated with DRESS include antiepileptics, antibiotics, antituberculosis, and non-steroidal anti-inflammatory agents (NSAIDs). Its diagnosis is sometimes made late and can become a challenge. The diagnostic criteria proposed by the international Registry of Severe Cutaneous Adverse Reactions (RegiSCAR) help to establish the diagnosis through a score system based on clinical and laboratory findings. The first step to identify the culprit is a thorough clinical history that includes all suspects, emphasizing those most known to cause DRESS syndrome according to the context and the literature. A skin biopsy may also be helpful in the diagnostic process. Patch testing is the test of choice to search for the culprit in cases of DRESS. Regarding prognosis, the estimated mortality due to DRESS is 3.8%. The main causes of mortality include fulminant hepatitis and liver necrosis. Several indicators of poor prognosis have been identified and these include an eosinophil count above 6000 × 103/μL, thrombocytopenia, pancytopenia, leukocytosis and coagulopathy. This article aims to review the evidence available regarding the epidemiology, pathophysiology, clinical and laboratory findings, diagnosis, and treatment of DRESS.